"They polluted our cropfields and our rivers, they killed us": Farmers' complaints about mining pollution in the Katangese Copperbelt. Issue 4 (April 2023) - Balasha, Arsene Mushagalusa; Peša, Iva
Abstract: The adverse impacts of mining industries on human health, local biodiversity, and food security are well-documented in the Katangese Copperbelt. However, farmers' perceptions of pollution and their struggles to obtain compensation for the externalities of mining industries are little addressed in scientific and public debates. Drawing on interviews with smallholder farmers, local civil society archives, oral histories, and analysis of satellite images, this article presents a case of farmers of Mulungwishi Valley whose fields and waterways were polluted by mining effluents. While 25% of respondent farmers argued that they had noticed pollution from the beginning of the 2000s, testimonies from civil society, customary authorities, and farmers concurred that the phenomenon has increased since 2010. Particularly between 2013 and 2014, the death of fish in the Mulungwishi River, the coloration of the water, the spread of mining effluents across the valley, and crop failure raised concerns and despair among farmers. Remarkable changes in land cover and use were noticeable. Since a joint impact assessment in 2014 by la Générale des Carrières et des Mines' (Gécamines) experts and farmers, civil society unsuccessfully continued a struggle to obtain compensation for about 2570 farmers affected by pollution. Despite an absolute silence of the polluter, 88% of these farmers insisted on the depollution of the valley and were willing to accept, if it was offered, financial compensation of US 2820 per farmer. The decade-long persistence of farmers in asserting these requests debunks the view of farmers as passive or not concerned about environmental pollution. This article will be helpful for stakeholders (victims and polluters) to find common ground when resolving this environmental issue that has resulted in socio-economic difficulties beyond the valley. Highlights: Mining companies and government officials have overlooked farmers' complaints about pollution in the Katanga copper belt. Polluted crop fields and rivers raised concerns and despair among smallholder farmers. Mining pollution resulted in cropland degradation, crop failure, and contamination of waterways. Despite the decade-long persistence of complaints, farmers have not received compensation for mining pollution.